Upaya Pencegahan Penyakit Degeneratif Melalui Pemeriksaan dan Edukasi Kesehatan Pada Lansia di Kelurahan Panau, Kecamatan Tawaeli: Pengabdian - Ririen Hardani; Yuliet; Andi Atirah Masyita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Aging is a natural process that increases the risk of health problems, with older adults often facing both physical and mental challenges. Efforts to improve public understanding of elderly health and the need for regular check-ups are essential. Health education from the Indonesian Pharmacists Association (IAI) plays a role in raising awareness about the correct use of medication. Regular health examinations for the elderly are important for early detection, prevention of complications, and appropriate treatment, covering blood pressure, blood sugar, cholesterol, weight, and height. This program involved older adults in Panau Village, Tawaeli District, using a participatory empowerment approach that emphasizes community involvement. The goal is to raise awareness of the importance of regular health tests to prevent degenerative diseases, provide routine check-ups, and deliver health education to the elderly and their families to encourage healthy lifestyles. Activities included cholesterol, blood sugar, uric acid, and blood pressure checks, as well as health education. The results of this community service program will be published in the Jurnal Pengabdian Masyarakat Indonesia (JPMI).